Management of Pyoderma in a Sloth Bear - Shalini A.S; Upadhye S.V; Dhoot V.M; Pawshe M.D; Kolangath S.M (The Indian Veterinary Journal, 2023)
A male sloth bear about 4.5 yrs was brought from Bramhapuri, Chandrapur (Dist.) to Wildlife Research and Training Centre, Gorewada, Nagpur with the history of injury at the abdominal region. On Clinical examination, it was found that the animal had intensepruritus, diffuse alopecia, purulent and foul smelling discharge with sloughing of skin at the ventral side of the abdomen. Skin scrapping revealed negative for mange and skin impression smear was found to be negative for yeast infection while Gram staining revealed gram positive cocci in clusters indicating staphylococcus infection. Haematological examination revealed neutrophilic leukocytosis. Serum Biochemistry (BUN, Cr, Total protein, albumin, Globulin, SGOT, SGPT, ALP) was within normal range. Based on clinical, haemato-biochemical and skin scrapping examination, it was confirmed to be a case of pyoderma. The animalwas treated with Inj. Amoxicillin and clavunate, Inj. Dipyroneand Inj.Phernaramine maleate given intramuscularly for a period of 7 days. Tab. Bcozyme C forte given perorally for a period of 30 days. Also, dressing of ventral abdomen was done by spraying povidine iodine. The Sloth made uneventful recovery.